1997
DOI: 10.1046/j.1365-2621.1997.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ice‐nucleation active bacteria on the freezing of some model food systems

Abstract: Cells of ice‐nucleation active (INA) bacteria, Pseudomonas syringae and Erwinia herbicola, were cultured at 18°C with media of nutrient broth and/or yeast extract and harvested at late log phase for maximum ice nucleation activity. These cells were able to nucleate water to freeze at temperatures as high as −2°C. They were incorporated into model food systems, including sugar, protein solutions and oil/water suspensions, representing all major components of foods, to investigate their effects on freezing. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 20 publications
1
20
0
1
Order By: Relevance
“…Cumulative INA, defined as the activity units at temperatures higher or equal to the bath temperature setting, was measured by the droplet-freezing method (Li et al, 1997;Vali, 1971). Samples were diluted so that the frozen fractions represented less than 40% of the total droplets.…”
Section: Methodsmentioning
confidence: 99%
“…Cumulative INA, defined as the activity units at temperatures higher or equal to the bath temperature setting, was measured by the droplet-freezing method (Li et al, 1997;Vali, 1971). Samples were diluted so that the frozen fractions represented less than 40% of the total droplets.…”
Section: Methodsmentioning
confidence: 99%
“…Other researchers also noted the reduction effect of ice-nucleation active bacteria on the freezing time. Li et al (1997) found that with the addition of P. syringae cells (10 7 CFU/mL), for 1%, 5% sucrose solution and 1%, 9% egg white solution cooled at À6.0°C, the freezing time savings from 15% to 20% were observed. Zasypkin and Lee (1999) found that the freezing time of a 10 mL water sample cooled at À10°C was cut by 28% with the addition of ice-nucleators from Pantoea ananas (5 Â 10 6 CFU/mL).…”
Section: Freezing Of Sucrose Solutionmentioning
confidence: 99%
“…They found that the texture, flavor and color of the foods were improved. Li et al (1997) incorporated P. syringae and Erwinia herbicola into model food systems, including sugar solution, protein solution and oil-water suspension. The incorporation led to the reduction of freezing time by 20-38% and improved the product quality when the cooling temperature was set at À6 to À7°C.…”
Section: Introductionmentioning
confidence: 99%
“…(i) pest control, by deliberate ice seeding of supercooled insects (Lee 1997); (ii) rapid test for Salmonella, by incorporating INA genes into specific bacteriophages (Worthy 1990); (iii) enhanced freeze concentration, by incorporating nucleators in the freezing mixture (Kumeno et al 1994); (iv) accelerated freezing of foods, with claimed energy savings by removal of supercooling (Li et al 1997); and (v) facilitated freeze drying, by increasing ice crystal sizes in the presence of INA actives (Watanabe & Arai 1987).…”
Section: Ice Nucleationmentioning
confidence: 99%